(untitled) (Research, Society and Development, 2022)
Acerola is a fruit which has stood out due to its high nutritional value. Because of its great market potential and of its increasing growth, there must be a constant attention when it comes to diseases and pests. Thus, the object of this work is to analyze alternative PET traps and more efficient natural baits in catching fruit flies in acerola cultivations. In order to get that done, traps have been installed in an acerola cultivation in a farm in the country side in Limoeiro de Anadia, state of Alagoas, located in the northeast Brazil. The completely randomized design, in factorial design 4x2x2 with 10 repetitions divided in time (5 repetitions for two seven days intervals), the treatment being: four types of natural baits: guava, acerola and orange natural fruit juice and, as witness, brown sugar diluted in water, and trap in two colors, transparent and green. The original data have been subjected to variation analysis by means of the Software R, and to a normality test of the residues (Shapiro -Wilk) to 5% of significance. As a whole 305 individuals were captured, divided in Anastrepha spp. And C.capitata, being the latter predominant. According to the total of flies captured, we could observe that there were no significative variation between the treatments and the PET bottles colors, and the average number of flies collected by the traps with different baits and different colors of PET bottles also were not different, being all the traps and baits efficient in catching the flies.